QoE Analysis of Open Access Network at the University of Riau - Anhar, Anhar; Putri, Sonia Maharani (International Journal of Electrical, Energy and Power System Engineering, 2023)
This journal outlines a QoE network analysis conducted through both subjective and objective methods. The subjective approach involved the distribution of questionnaires via Google Forms to Riau University students using open access network, while the objective method utilized open access network in the Engineering Faculty Lobby and the Riau University Library, facilitated by the Google LightHouse tool. This analysis extended over a span of five days, encompassing morning, afternoon, and evening measurements, focusing on five web-based applications: YouTube, Facebook, WhatsApp, Instagram, and the Riau University Portal. The parameters assessed included Performance, Accessibility, Best Practices, and SEO. The QoE measurement results were presented in both tabular and graphical formats. The subjective method yielded a MOS value of 3.45, classifying it as "quite good." Meanwhile, when using the objective method in the open access network in the Lobby of the Faculty of Engineering, the average performance was 46.86, placing it in the "bad" category. In the UNRI Library location, the average performance was 48.2, also categorized as "bad." However, for other parameters, the average scores exceeded 50, falling into the "Fair" and "Good" categories.